(untitled) (International relations and international law Journal, 2016)
International attention to the issue of pesticides, as well as the facts on the health effects of pesticides once again prove the need for regular inventory of hazardous chemicals, including obsolete, unusable and banned for use pesticides and pesticides out of persistent organic pollutants. Inventory of possible sources of pesticides in the environment allows to identify contaminated territory, stocks of obsolete and banned pesticides, pockets of unregistered chemicals and to propose environmentally best ways to eliminate them. The group of agricultural chemicals (pesticides) includes hundreds of substances of different chemical compositions, physical properties, toxicity and purposes of use. As a rule, national legislation aimed at establishing the right balance between risks and benefits of these substances that are used intentionally and are aimed at reducing pollutants in accordance with a high level of consumer protection. For Kazakhstan, the problem of food security and environmental protection issues are particularly relevant in connection with the ongoing changes in recent years in all areas of the country, as well as on the eve of accession to the WTO.